Anticonvulsant Effects of Synthetic N-(3-Methoxybenzyl)oleamide and N-(3-Methoxybenzyl)linoleamide Macamides: An In Silico and In Vivo Study - Karin Jannet Vera-López; Jorge Alberto Aguilar-Pineda; Rodrigo Martín Moscoso-Palacios; Gonzalo Davila-Del-Carpio; José Luis Manrique-Murillo; Badhin Gómez; Minerva González-Melchor; Rita Nieto-Montesinos (Molecules)
Epilepsy is a chronic neurological disorder that affects nearly 50 million people worldwide. Experimental evidence suggests that epileptic neurons are linked to the endocannabinoid system and that inhibition of the FAAH enzyme could have neuroprotective effects by increasing the levels of endogenous endocannabinoid anandamide. In this context, the use of macamides as therapeutic agents in neurological diseases has increased in recent years. With a similar structure to anandamide, several theories point to the FAAH–macamide interaction as a possible cause of FAAH enzymatic inhibition. In this work, we used in silico and in vivo techniques to analyze the potential therapeutic effect of three synthetic macamides in the treatment of epilepsy: N-3-methoxybenzyl-oleamide (3-MBO), N-3-methoxybenzyl-linoleamide (3-MBL), and N-3-methoxybenzyl-linolenamide (3-MBN). In the first stage, an in silico analysis was conducted to explore the energetic affinity of these macamides with rFAAH and their potential inhibitory effect. MD simulations, molecular docking, and MM/PBSA calculations were used for these purposes. Based on our results, we selected the two best macamides and performed an in vivo study to analyze their therapeutic effect in male Sprague Dawley rat models. Rats were subjected to an in vivo induction of epileptic status by the intraperitoneal injection of pilocarpine and analyzed according to the Racine scale. In silico results showed an energetic affinity of three macamides and a possible “plugging” effect of the membrane access channel to the active site as a potential cause of FAAH inhibition. On the other hand, the in vivo results showed an anticonvulsant effect of both macamides, with 3-MBL being the most active, resulting in a higher survival probability in the rats. This work represents one of the first studies on the use of macamides for the treatment of epilepsy.